1990
DOI: 10.1093/infdis/161.6.1170
|View full text |Cite
|
Sign up to set email alerts
|

Binding of  -Lactam Antibiotics to Penicillin-Binding Proteins in Methicillin-Resistant Staphylococcus aureus

Abstract: Binding affinity of penicillin-binding proteins (PBP) of Staphylococcus aureus for several beta-lactam antibiotics was examined in a methicillin-susceptible strain and in two methicillin-resistant strains, one heterogeneous and one homogeneous, to determine relationships between PBP binding and expression of resistance. PBPs 1-4 had similar affinities in all three strains. PBP 2a affinities were similar in both resistant strains. For the susceptible strain and for the susceptible subpopulation of cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
3
5

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 33 publications
6
96
3
5
Order By: Relevance
“…While a few clinical isolates of MRSA express homogeneous oxacillin resistance (i.e., Ն1 in 10 2 cells express high-level resistance), the majority of isolates have heterogeneous drug resistance (heteroresistance) (5,6,13). Phenotypic expression of resistance can vary depending on the growth conditions (e.g., the temperature or osmolarity of the medium), making susceptibility testing of MRSA by standard microbiological methods potentially problematic (5).…”
Section: Of the 2 Million Annual Nosocomial Infections In The Unitedmentioning
confidence: 99%
“…While a few clinical isolates of MRSA express homogeneous oxacillin resistance (i.e., Ն1 in 10 2 cells express high-level resistance), the majority of isolates have heterogeneous drug resistance (heteroresistance) (5,6,13). Phenotypic expression of resistance can vary depending on the growth conditions (e.g., the temperature or osmolarity of the medium), making susceptibility testing of MRSA by standard microbiological methods potentially problematic (5).…”
Section: Of the 2 Million Annual Nosocomial Infections In The Unitedmentioning
confidence: 99%
“…3 In our study 18 Staphylococcus aureus showed the MIC of 4 g/ml suggesting high incidence of MRSA from non-clinical specimens. Of the total Staphylococcus aureus isolated, 87.5% were resistant to multiple class of drugs.…”
mentioning
confidence: 47%
“…1,3 MRSA is a major cause of morbidity and mortality both in healthcare settings and in healthy individuals in the last two decades. The global emergence and spread of MRSA harbouring multi-resistance genes limits the effectiveness of therapeutic options for staphylococcal infections and worsens their clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBP2a has probably evolved by recombination of a penicillinase gene and a PBP gene similar to PBP2 and PBP3 of Escherichia coli (255). PBP2a has an unusually low binding affinity for all beta-lactam antibiotics, substituting the native PBPs and allowing continuous cell wall assembly (36,228). However, the production of PBP2a alone is not sufficient for optimal expression of methicillin resistance (216).…”
Section: Methicillin Resistancementioning
confidence: 99%